The causal relationship between information and communication technology and foreign direct investment - Roghieh Gholami; San-Yong Tom Lee; Almas Heshmati (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2003)
This paper investigates the simultaneous causal relationship between investments in information and communication technology (ICT) and foreign direct investment (FDI), with reference to its implications on economic growth. For the empirical analysis we use data from 23 major countries with heterogeneous economics development for the period 1976–99. The results of unit roots and Johansen co-integration tests indicate variations in degrees of integration among the sample countries. Our causality test results suggest that there is a causal relationship from ICT to FDI interpreted as the higher level of ICT investment leads to increased inflow of FDI. ICT contributes to economic growth indirectly by attracting more foreign direct investment. In developed countries there already exist a build up ICT capacity which causes inflow of FDI, while in developing countries ICT capacity must be build up to attract FDI. The inflow of FDI causes further increases in ICT investment and capacity.
Keywords: C23; C33; C51; E22; F21; 330; foreign direct investment; FDI; information and communication technology; ICT; stationarity; co-integration; causality; Informationstechnik; Direktinvestition; Welt